FENOMENA PENGEMIS DI KOTA LANGSA - Ade Fadillah FW Pospos (FEBI IAIN Langsa, 2017)
This study aims to determine the factors that cause a person to be a beggar in terms of structural and cultural factors. This study uses Grounded research. The resulting data are descriptive and the analysis is done inductively and this research is more emphasis on meaning than generalization. Data analysis technique used is based on constant comparative with descriptive strategy. The results of the research indicate that the structural factors that cause the community to become beggars are: 1) the education of beggars who are mostly only elementary school graduates, this causes them to have no formal skills so they can not be accepted to work in any company. 2) government assistance is not maximal, so they continue to get caught in poverty and prefer to become beggars to fulfill their life. Cultural factors that cause them to be beggars are: 1) Resigned, this is caused by the lack of capital given the government so that they live in poverty , 2) has no vision and mission of life, so there is no intention of the beggar to change his destiny.